SEJARAH DAN PEMBANGUNAN DI KEPULAUAN RIAU - Ali Yusri (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2006)
This paper try to view history and development of Riau Island. Period of development Riau Island t be focused, and several variable including. The method using historical aproach, interview key informan and secondary data to support writing narative. The conclusion of this paper, the pretending of development on Riau Island full of dynamic dialetic and central state hegemony.